Revision of Sciasmomyia Hendel (Diptera: Lauxaniidae), with eight new species - Shi, Li; Gaimari, Stephen D.; Yang, Ding (Zootaxa, 2013)
The genus Sciasmomyia Hendel is revised. Eight new species are proposed, including Sciasmomyia decussata sp. nov. (China), S. leishanensis sp. nov. (China), S. longicurvata sp. nov. (China), S. longissima sp. nov. (China), S. lui sp. nov. (China), S. quadricuspis sp. nov. (China), S. thaii sp. nov. (Vietnam), and S. tubata sp. nov. (China). The two previously known species, Sciasmomyia meijerei Hendel and S. supraorientalis (Papp), are recorded for the first time as occurring in China, with the latter species also newly recorded for India, Nepal and Thailand. A key to separate the 10 species of this genus is presented, and a lectotype is designated for Sciasmomyia meijerei.